Comparative assessment of bone mineral density in recipients with preserved function and calcium degeneration of heart valve bioprotheses - N. V. Rutkovskaya; A. N. Stasev; N. V. Kondyukova; O. K. Kuzmina; V. B. Fanaskov; L. P. Barbarash (Российский кардиологический журнал, 2018)
Aim. To study a bone mineral density (BMD) in recipients with calcium degeneration and preserved morphofunctional state of heart valve bioprotheses (BP).Material and methods. The experimental groups included the patients with structural dysfunctions of BP associated with the calcification of the xenomaterial, confirmed by light and electron microscopy data (group I, n=22) and the patients with normal functional state of the implanted valves according to the results of echocardiographic tests (group II, n=48). BMD was assessed by dual energy absorptiometry in the absolute count of mineralized bone and indicators of Ttest.Results. When interpreting the Ttest of a femoral neck the severity of osteopenic syndrome prevailed in patients with calcium degeneration of BP (1,83 [2,66; 1,25] in group I vs 1,47 [2,51; 0,86] in group II, р=0,055). At that the mean values of this indicator in patients with the development of calciumassociated BP dysfunctions in the first four years after a surgical correction of the defects reached the diagnostic criteria of the osteoporosis (2,73 [3,40; 2,09] vs 1,67 [2,92; 0,42], р>0,05). According to the result of absorptiometry of the lumbar spine the worst Тscore indicators were also recorded in recipients with the calcification of BP within the first four years of followup (1,75 [1,83; 1,43] vs 0,81 [0,96; 0,66] in patients without the signs of calcification, р=0,021). The state of BMD reflects the physiological and pathological processes of calcium redistribution in organism. The existence of the pathogenetic parallels between the activity of bone resorption processes and calcification of the elements of cardiovascular system allows to consider the osteopenia and pathological mineralization of the soft tissues within the framework of a single continuum. The results of the presented work in their turn testify to the determining significance of the severity of osteopenic syndrome manifestations in the development of the “early” calcium degeneration of BP.Conclusion. Extension of the concepts of the mechanisms and processes which form the pathogenetic basis of mineralization will allow to determine the effective strategies for managing the risk of calciumassociated BP dysfunctions.